Nematodes in the Scots pine wood in the bark beetles foci within Rivne region - Andreieva, O. Yu. (Forestry and Forest Melioration, 2021)
Introduction According to some research, the nematodes have contributed to the deterioration of the health condition of Scots pine stands in recent years by clogging the tracheids of early wood. Entomophilic, phytophagous, saproxylic, and associated with fungi nematode species were found in drying Scots pine trees in Polissia in previous years. Since the phytophagous nematode was found only in drying trees in bark beetle foci, it cannot be argued that it was the nematodes that caused the weakening of those trees. The aim of the research was to identify the species composition and distribution by ecological and trophic groups of nematodes isolated from the wood of Scots pine trees in the bark beetles’ foci. Materials and Methods The study was carried out in Krichilske forestry of the Sarny State Forest Enterprise. Wood samples to determine the species composition, distribution, and density of nematode populations were taken from model trees - 3 trees of the 3rd and 6th categories of health condition from two sample plots, 12 model trees in total. Nematodes were isolated from wood samples in the laboratory using the Baermann method. The nematodes were identified by morphometric characteristics. The frequency of occurrence of nematode species was evaluated as the proportion of samples with the presence of particular species from all examined samples. Results and Conclusions In 55 % of the wood samples of Scots pine trees, 16 species of nematodes from 12 genera, 10 subfamilies, 9 families, 6 superfamilies, 4 suborders, and 3 orders were identified. No significant differences in the nematode species composition in the samples from dry poor and relatively poor fresh forest site conditions were found. The frequency of occurrence of nematodes in the trees of the 6th category of health condition is significantly higher than in those of the 3rd category. By population density in 100 g of wood, saproxylic, phytophagous, entomophilic, and associated with fungi nematode species were 53; 24.7; 12 and 10.3%, respectively. B. mucronatus was found in the stem part with transitional bark, B. chitwoodi with thin bark, B. eggersi with thin and thick bark, and entomohelminths with thick bark.